2017
DOI: 10.5664/jcsm.6500
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulin Therapy in Pediatric Narcolepsy: A Nonrandomized, Open-Label, Controlled, Longitudinal Observational Study

Abstract: Study Objectives: Previous case reports of intravenous immunoglobulins (IVIg) in pediatric narcolepsy have shown contradictory results. Methods: This was a nonrandomized, open-label, controlled, longitudinal observational study of IVIg use in pediatric narcolepsy with retrospective data collection from medical files obtained from a single pediatric national reference center for the treatment of narcolepsy in France. Of 56 consecutively referred patients with narcolepsy, 24 received IVIg (3 infusions administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 34 publications
2
20
0
1
Order By: Relevance
“…Several pieces of evidence support an autoimmune mechanism underlying the onset of NT1, offering a rationale for the use of immunomodulation therapy with intravenous immunoglobulin G (IVIG) close to disease onset. Only a few investigators [39,[90][91][92] have tried IVIG in early-onset narcoleptic patients to understand its therapeutic efficacy, but the results are controversial due to the small sample size, openlabel design, and self-report observations. The results suggest a potential improvement in frequency and severity of cataplexy and ameliorated daytime sleepiness, data further confirmed by new evidence [93].…”
Section: Immunotherapymentioning
confidence: 99%
“…Several pieces of evidence support an autoimmune mechanism underlying the onset of NT1, offering a rationale for the use of immunomodulation therapy with intravenous immunoglobulin G (IVIG) close to disease onset. Only a few investigators [39,[90][91][92] have tried IVIG in early-onset narcoleptic patients to understand its therapeutic efficacy, but the results are controversial due to the small sample size, openlabel design, and self-report observations. The results suggest a potential improvement in frequency and severity of cataplexy and ameliorated daytime sleepiness, data further confirmed by new evidence [93].…”
Section: Immunotherapymentioning
confidence: 99%
“…We have reported a patient with a dramatic, but again unfortunately temporary, improvement of symptoms after treatment with rituximab [74]. The largest study so far on the immunomodulatory treatment in pediatric narcolepsy is a non-randomized controlled open-label trial in France [75]. In this study, a subset of patients with the highest scores in the narcolepsy screening questionnaire Ullanlinna Narcolepsy Scale (UNS) had remission of symptoms sooner than those who were not treated with IVIg.…”
Section: Treatmentmentioning
confidence: 81%
“…It has been shown that the loss of HCRT is still ongoing close to symptom onset in some patients [19], and there is thus a great clinical need for immunomodulatory treatment options. Therapies such as corticoids and intravenous immunoglobulins have however shown mostly a disappointing lack of efficacy [20][21][22]. Such therapies mainly target the humoral immune system.…”
Section: Treatment Of Nt1 With Immunosuppressive Therapychallenges Anmentioning
confidence: 99%